Intraseasonal Linkages of Winter Surface Air Temperature Between Eurasia and North America - Xiaocen Shen; Lin Wang; Adam A. Scaife; Steven C. Hardiman (Geophysical Research Letters)
Abstract Wintertime temperature extremes sometimes show a continental linkage between Eurasia and North America (NA), but whether these connections are coincidental or dynamically robust remains unclear. This study investigates the linkages of the leading intraseasonal temperature patterns between Eurasia and NA, focusing on the underlying dynamic processes. Our findings reveal a weak but robust linkage between the dominant patterns in both regions. Specifically, an opposite‐phase temperature anomaly in NA occurs about 1 week after a Eurasian temperature anomaly, influenced by wave propagation in both the troposphere and stratosphere. Conversely, a same‐phase temperature anomaly appears over central Eurasia approximately 1 week after a North American temperature anomaly, primarily driven by a Scandinavian‐like pattern in the troposphere. These relationships sometimes overlap, forming a sequence of temperature changes across mid‐high latitudes, closely tied to the stratosphere‐troposphere coupling process. The findings provide new insights for a more comprehensive understanding of wintertime intraseasonal temperature variability.